(untitled) (Research, Society and Development, 2022)
Cervical cancer, also called cervical cancer, is caused by persistent infection with some types of Human Papillomavirus. Genital infection by this virus is very common and most of the time it does not cause illness. In some cases, cellular changes occur that can progress to cancer. Therefore, the objective of this study is to report the experience of a team of academics from courses in the health area, carried out in a Municipal Health Unit in the city of Belém. This is a descriptive study, with a qualitative approach, of the experience report type, in which we seek to understand the relationships developed based on different contexts. In short, the importance of promoting care for a better quality of life was confirmed, as well as the need to encourage preventive measures against cervical cancer. The study made it possible to report the experience of academics in the face of educational and recreational activities carried out, where it was possible to pass on and acquire knowledge about the subject addressed, how to encourage the realization of preventive exams, thus being able to minimize cases of death from cervical cancer and thus aiming to raise awareness about the importance of educational practices in health units in order to contribute to the propagation of information for self-knowledge.